2020
DOI: 10.1002/2211-5463.12942
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine‐like factor 1 (CKLF1) aggravates neointimal hyperplasia through activating the NF‐κB /VCAM‐1 pathway

Abstract: Neointimal hyperplasia (NIH) plays a pivotal role in vascular restenosis after revascularization. We previously identified that chemokine‐like factor 1 (CKLF1) could aggravate NIH by arresting smooth muscle cells in G2/M phase and preventing apoptosis via phosphoinositide 3‐kinase/AKT/nuclear factor‐kappa B signaling. Here, we demonstrate that CKLF1 promotes monocyte adhesion and smooth muscle cell migration via VCAM‐1. Our work furthers our understanding of how CKLF1 contributes to NIH causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Previous research has shown that VCAM-1 is closely related to restenosis in venous bridges 36,37 . VCAM-1 belongs to the immunoglobulin superfamily and can be expressed in endothelial cells, smooth muscle cells, and macrophages 38 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has shown that VCAM-1 is closely related to restenosis in venous bridges 36,37 . VCAM-1 belongs to the immunoglobulin superfamily and can be expressed in endothelial cells, smooth muscle cells, and macrophages 38 .…”
Section: Discussionmentioning
confidence: 96%
“…It was found that the expression of CKLF1 and vascular adhesion molecule-1 (VCAM-1) was significantly increased in human carotid plaques compared to controls. Meanwhile, CKLF1 promoted the aggregation of human aortic smooth muscle cells (HASMCs) and monocyte adhesion through the NF-κB/VCAM-1 pathway ( 71 ).…”
Section: Cklf1-related Diseasesmentioning
confidence: 99%
“…Unlike other ligands of CCR4, such as TRAC and MDC, CKLF1 can activate the NF-κB classical signaling pathway involved in disease-causing mechanisms, which may have to do with its specific structure. A study on human amniotic mesenchymal stromal cells showed that CKLF1 mediates monocyte adhesion and smooth muscle cell (SMC) migration through the NF-κB/VCAM-1 pathway and that the use of PDTC, an NF-κB inhibitor, suppressed the CKLF1-induced elevation of VCAM-1 ( 71 ). A mouse MCAO model study showed that CKLF1 binding to CCR4 activated the NF-κB pathway and promoted microglia/macrophage polarization toward the M1 phenotype ( 49 ).…”
Section: Mechanisms Of Cklf1-mediated Pathogenesismentioning
confidence: 99%
“…For instance, the findings of a study by Liu et al ( 17 ) suggest that CKLF1 serves an oncogenic role in the tumorigenesis and metastasis of hepatocellular carcinoma. CKLF1 contributes to neointimal hyperplasia via the activation of the NF-κB/vascular cell adhesion molecule 1 signaling pathway ( 18 ). Additionally, Pan et al ( 19 ) proposed that CKLF1 exhibits higher expression in necrotic cartilage tissues compared with normal cartilage tissues.…”
Section: Introductionmentioning
confidence: 99%